A nutritional intervention for moderate altitude endurance preparation: A case report. Issue 1 (31st December 2022) - Guerrero-Pinzón, Juan J.; Alcantara, Juan M.A.; García-Buendia, Gustavo; Mochón-Benguigui, Sol; Ramírez-Maldonado, Mauricio; Ruiz, Jonatan R.; Jurado-Fasoli, Lucas
ABSTRACT: Background: Moderate altitudes carry physiological and metabolic changes that can dampen exercise performance. Fortunately, these changes can be modulated by an optimal nutritional intervention. This case study represents the first nutritional intervention of a moderate altitude athlete. These results may help to establish well-designed nutritional guidelines for moderate altitude sports athletes. Case presentation: This case study examined the effects of a 11-week nutritional intervention on body composition, muscle strength, cardiorespiratory fitness, resting and exercise nutrient oxidation, and subjective sleep quality, in a male high-level moderate altitude athlete with a very light non-exercise activity thermogenesis. During the 11-week of nutritional intervention, 2800-3500 kcal/day, 6.8-8.9 g/kg/day of carbohydrates, 1.2-1.7 g/kg/day of protein, and 1-2.5 g/kg/day of fat were prescribed. Different specific considerations were also included, such as: iron supplementation, antioxidants increment in different phases, and ergogenic aids (i.e. creatine and beta-alanine). Our results demonstrated a decrease in adiposity and an increase in fat-free mass. In parallel, the athlete improved muscle strength, and therefore endurance adaptations after a maximal effort test (i.e. enhancement of the heart rate recovery). After the intervention, the athlete not only increased the carbohydrate oxidation during exercise and resting conditions but also improved his subjective sleep quality. Conclusions: Our results suggest that a nutritional intervention based on the endurance nutritional recommendations and adapted to the altitude physiological peculiarities can induce body re-composition, improve physiological adaptations to effort, and upgrade the substrate oxidation in a moderate altitude high-level athletes.